Rb–Sr whole-rock age of the Klondike Schist, Yukon Territory - Metcalfe, P.; Clark, G. S. (Canadian Journal of Earth Sciences, 1983)
Seven samples of metarhyolite from a measured section of the Klondike Schist, in the Yukon Crystalline Terrane, 5 km southwest of Dawson City, give a whole-rock Rb–Sr isochron age of 202 ± 11 Ma with an initial 87 Sr/ 86 Sr ratio of 0.7140 ± 0.0001. The high initial ratio suggests that this is a metamorphic age, recording the time of shearing of the metarhyolites. An estimated minimum age of formation of the protolith of approximately 260 Ma was obtained by rotating the isochron to an assumed primary initial 87 Sr/ 86 Sr ratio of 0.707.The siliceous cataclasites of the Klondike Schist may have formed as a forearc wedge of arkose with intercalated volcanics. The unit was intensely sheared in a subduction zone, prior to obduction onto the ancient North American continental margin. The results of this isotopic study suggest an age of formation of 260 Ma and an age of cataclasis of 202 Ma. The metarhyolites remained closed to Rb–Sr isotopic equilibration during obduction, though the thermal event is recorded in K–Ar isotopic data reported by other authors. The results of this study are consistent with theories of formation of this assemblage.